Dampak Kebijakan Fiskal Terhadap Pertumbuhan Ekonomi Di Negara Berkembang - Lase, Forlin (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Fiscal policy is the government's primary instrument for managing macroeconomic stability. In developing countries, the role of fiscal policy is crucial yet complex due to limited fiscal space and vulnerability to external shocks. This paper analyzes how government spending and tax policy affect economic growth. The review shows that productive spending (infrastructure and education) has a positive long-term impact, while uncontrolled budget deficits risk hindering growth through a crowding-out effect.